Peyton Place (1957) [videorecording (DVD)] - Robson, Mark, 1913-1978; Turner, Lana, 1921-1995; Lange, Hope; Moore, Terry, 1929-; Tamblyn, Russ; Kennedy, Arthur, 1914-1990; Nolan, Lloyd; Metalious, Grace (Studio classic, 2004)
Allison MacKenzie looks back on life in the New England town where she grew up around the time of Pearl Harbor. Beneath the town's placid god-fearing exterior lay any number of dark secrets.